Guidance and surroundings awareness in outdoor handheld augmented reality - Rovira, Aitor (PLoS One, 2020)
Handheld and wearable devices are becoming ubiquitous in our lives and augmented reality technology is stepping out of the laboratory environment and becoming ready to be used by anyone with portable devices. The success of augmented reality applications for pedestrians depends on different factors including a reliable guidance system and preventing risks. We show that different guidance systems can be supplementary to provide directions to a point of interest and offer clues that help the user find the augmented data when they get close to the location they have to visit. We tested the helpfulness of a map with the points of interest, an image preview of the next point of interest to visit, and an arrow showing the direction to it. The results show that the effectiveness of these guidance systems depend on the distance to the point of interest and the accuracy of the data obtained from the Global Positioning System. We also measured the total time that participants spent looking at the screen, as well as the perceived elapsed time as a measurement of real world dissociation. Finally, we discuss preliminary results to minimize the risk of accidents when using augmented reality applications in an outdoor urban environment.